Over-the-counter antibiotics in Saudi Arabia, an urgent call for policy makers - Sharafaldeen Bin Nafisah; Salahaldin Bin Nafesa; Aliyah H. Alamery; Mazen A. Alhumaid; Haitham M. AlMuhaidib; Fahad A. Al-Eidan (Elsevier, 2017)
Antibiotics over-consumption is a pandemic that has a tremendous cost on the overwhelmed healthcare system. The accessibility of antibiotics coupled with the misconception of public toward those drugs both of which implicated in the use and misuse of antibiotics. The aim of this study was to investigate the perception of the community toward antibiotics, its purpose and harmfulness, in addition to the accessibility of those drugs as over the counter and without prescriptions. We also investigated the behavior toward antibiotic prescriptions when perceived unnecessary. This is a cross-sectional study in Riyadh-Saudi Arabia based upon a structured self-administered questionnaire. The study included 473 individuals with a mean age of 27 years old. Forty eight percent (n = 227) of the participants obtain antibiotics without prescriptions. Ninety two percent (n = 208) of those noted pharmacist counseling as their method of acquisition. Self-prescription noted in 8.4% (n = 19). Viral illnesses accounted for the highest percentage for seeking antibiotics in 35.5% (n = 166) more commonly among females. Thirty one point eight percent (n = 149) used antibiotics for analgesia while 13.7% (n = 64) believed in their prophylactic use. We also noted that the prevalence of sharing antibiotics is 19.7%. The perceived unnecessary prescriptions uncovered 122 of the participants who reported throwing the prescribed antibiotics away after acquisition. Dispensing antibiotics without prescription is an issue that mandates a political intervention and implementation of the existing laws that prohibit dispensing without proper prescription. We advocate public health measures targeting both healthcare providers and the public on the use and misuse of antibiotics. Keywords: Over the counter antibiotics, Antibiotics without prescriptions, Prudent use of antibiotics